Efficient Web Service Selection Approaches: A Review - Neerja Negi, Satish Chandra (International Journal of Advanced Science and Technology, 2020)
Toward everybody’s life, the growth of information technology has put a significant influence. Nowadays, information technology is available in offices, homes, and businesses on a large-scale. In this scenario, web services are playing an essential role in the expansion of innovative upcoming technologies similar to IoT & cloud computing. Therefore, businesses are utilizing web services to offer various services to their consumers. But, the extensive amount of web services offers identical services. Therefore, this is an extremely challenging task to choose the most reliable one. This paper has provided a review of various techniques that are proposed by the researchers to determine the preferable efficient web services. The proposed paper has focused upon the strengths and the weaknesses of previously existing approaches, as well as it have also provided a base for new techniques.